Evaluation of a national data set for insights into sources, composition, and concentrations of per- and polyfluoroalkyl substances (PFASs) in U.S. drinking water. (May 2018) - Guelfo, Jennifer L.; Adamson, David T.
Abstract: The United States Environmental Protection Agency (USEPA) completed nationwide screening of six perfluoroalkyl substances in U.S. drinking water from 2013 to 2015 under the Third Unregulated Contaminant Monitoring Rule (UCMR3). UCMR3 efforts yielded a dataset of 36, 139 samples containing analytical results from >5000 public water systems (PWSs). This study used UCMR3 data to investigate three aspects of per- and polyfluoroalkyl substances (PFASs) in drinking water: the occurrence of PFAS and co-contaminant mixtures, trends in PFAS detections relative to PWS characteristics and potential release types, and temporal trends in PFAS occurrence. This was achieved through bivariate and multivariate analyses including categorical analysis, concentration ratios, and hierarchical cluster analysis. Approximately 50% of samples with PFAS detections contained ≥2 PFASs, and 72% of detections occurred in groundwater. Large PWSs (>10, 000 customers) were 5.6 times more likely than small PWSs (≤10, 000 customers) to exhibit PFAS detections; however, when detected, median total PFAS concentrations were higher in small PWSs (0.12 μg/L) than in large (0.053 μg/L). Bivariate and multivariate analyses of PFAS composition suggested PWSs reflect impacts due to firefighting foam use and WWTP effluent as compared to other source types for which data were available. Mann-Kendall analysis of quarterly total PFAS detection rates indicated an increasing trend over time (p = 0.03). UCMR3 data provide a foundation for tiered design of targeted sampling and analysis plans to address remaining knowledge gaps in the sources, composition, and concentrations of PFASs in U.S. drinking water. Graphical abstract: Image 1 Highlights: Analysis of data from nearly 37, 000 drinking water samples collected in the U.S. and analyzed for per- and polyfluoroalkyl substances (PFASs). Samples nationwide contain measureable levels of PFAS mixtures and other co-contaminants such as 1, 4-Dioxane. Data highlight a need for additional, targeted evaluation of small public water systems, private wells, and occurrence of a broader suite PFASs. Abstract : PFASs occur in public water systems throughout the U.S.; concentrations and composition are dominated by mixtures of PFASs and other co-contaminants.